108. Immune Status of Indian Pediatric Health Care Workers against Various Vaccine Preventable Diseases. (15th December 2022) - Verma, Sanjay; Sachdeva, Ravinder Kaur; Mahajan, Vidushi; Rawat, Amit; Nehra, Urvashi; Subramani, Vignesh; Jassal, Monika; Bharti, Bhavneet
Abstract: Background: Health care workers (HCWs) possess a potential risk to acquire and spread various infections. This study was planned to assess the immune status of HCWs in pediatric departments of two tertiary care hospitals in Northern India. Methods: In this cross-sectional study, HCW's (Indians), working in pediatric departments of these hospitals, over 6-months period (July18-Dec18) were enrolled after taking written consent and their 5-ml venous blood sample was collected. Ethical clearance was obtained from Institute Ethics committee, before enrolling subjects. Serum were tested for antibodies against diphtheria-toxin (DT), pertussis-toxin (PT), measles, mumps, rubella, varicella, hepatitis-B (HbsAb) and hepatitis-A using commercial IgG (quantitative) ELISA kits. Results: A total of 160 HCW's (M:F=77:83), having mean age 30.6±7.8 years, were enrolled. Out of them 106 (66.3%) were resident doctors, 31 (19.4%) nursing-staff, 18 (11.3%) faculty members, 3 (1.9%) research-staff and 2 (1.3%) paramedical-staff. In our study, antibodies (IgG) against DT were between 0.01 to 0.1 IU/ml in 78.1% (120/160); requiring a Tdap booster; while 7 out of 125 had titers < 0.01 IU/ml, which needed 3-doses of primary vaccination. Antibodies (IgG) against PT < 30 IU/ml were seen in 60.6% (97/160), which were considered as seronegative, as per kit recommendations. A total of 3% (5/160), 13.1% (21/160), 10% (16/160), 17.5% (28/160) had titers < 12 IU/ml for IgG antibodies against measles, mumps, rubella and varicella respectively; were considered unprotected. A total of 25% (40/160) had Anti-HBs antibody titers < 20 mIU/ml; which were low, therefore were advised to take one booster dose of Hep-B vaccine. A total of 15.6% (25/160) had IgG antibodies against hepatitis-A < 10 mIU/ml; were unprotected. Conclusion: Alarming proportions of pediatric-HCWs had low antibody titres against DT (78.1%) and PT (60.6%), necessitating a dose of Tdap. A total of 10%, 17.5% and 15.6% lacked protective antibodies against rubella, varicella and hepatitis-A. A quarter of screened population had low anti-Hbs titres, requiring boosting of immunity. Our study emphasizes the urgent need for improving immunization status of pediatric HCW's; as they continue to remain susceptible to various vaccine preventable infectious diseases. Disclosures: All Authors : No reported disclosures.